Correction of Paradigms of University Pedagogical Process to Accelerate the Professional Growth of Engineers of Railway Transport - Roman Sushchenko (Pedagogical Discourse, 2014)
The article highlights the basic directions of renovation and prevision of proper psychologic-pedagogical preparation of the future engineers of railway transport to forming communicativeness as professional quality and organizational component of managerial culture. Conceptual paradigms and topical problems of professional preparation of engineers of railway transport in higher educational establishments have been analyzed. The directions, conditions of renovation of this process, taking into account modern market conditions and peculiarities of development under these conditions the branch of railway transport have been grounded. On the basis of the results of the analysis of scientific literature, the peculiarities of paradigm changes and their influence over formation of professionalism of the future railwaymans have been determined and grounded.